Community Health Centers : A Movement and the People Who Made It Happen - Lefkowitz, Bonnie (Book collections on Project MUSE., 2007)
The aftermath of Hurricane Katrina has placed a national spotlight on the shameful state of healthcare for America's poor. In the face of this highly publicized disaster, public health experts are more concerned than ever about persistent disparities that result from income and race. This book tells the story of one groundbreaking approach to medicine that attacks the problem by focusing on the wellness of whole neighborhoods. Since their creation during the 1960s, community health centers have served the needs of the poor in the tenements of New York, the colonias of Texas, the working class neighborhoods of Boston, and the dirt farms of the South. As products of the civil rights movement, the early centers provided not only primary and preventive care, but also social and environmental services, economic development, and empowerment. Bonnie Lefkowitz-herself a veteran of community health administration-explores the program's unlikely transformation from a small and beleaguered demonstration effort to a network of close to a thousand modern health care organizations serving nearly 15 million people. In a series of personal accounts and interviews with national leaders and dozens of health care workers, patients, and activists in five communities across the United States, she shows how health centers have endured despite cynicism and inertia, the vagaries of politics, and ongoing discrimination.